Extended Project on Farmer Managed Irrigated Agriculture Under The National Drainage Program (NDP): Water Distribution Equity in Sindh Province, Pakistan - Murray-Rust, Hammond; Lashari, Bakhshal K.; Memon, Yameen (International Water Management Institute, 2000)
The concept of equity of water distribution is widely used in assessment of irrigation water management performance; but in reality there is considerable confusion between the concepts of equity and equality. This research forms part of a larger study of Farmer Managed Irrigation in Sind Province.